Changes in household income, food consumption, and diet quality in urban and rural areas of Ghana during the COVID-19 crisis: Results of 2020 phone surveys - Ragasa, Catherine; Amewu, Sena; Asante, Seth (International Food Policy Research Institute, 2021)
This study provides an assessment of changes in household income, livelihood sources, food consumption, and diet quality during the first months of the COVID-19 crisis in a sample of households drawn from both urban and rural areas in Ghana. Phone surveys were conducted in June 2020 with 423 urban consumers in Accra and with 369 small-scale crop and fish farmers in rural areas in six regions in middle and southern Ghana. Data was disaggregated by asset quintiles for both the urban and the rural samples. Reduction in incomes were reported by 83 percent of urban households in Accra, mainly due to business closures and lower sales from their trading enterprises. Most households, however, are showing resilience in terms of food consumption, with a majority of urban consumers surveyed maintaining their pre-COVID-19 level of food consumption; only 9 percent of urban consumers reported reductions in food consumption to cope with income loss due to COVID-19. For the respondents in the rural areas in middle and southern Ghana, 76 percent reported income loss, and all reported that their livelihoods had been affected. Thirty-four percent of 2020 minor season crop farmers experienced difficulty in selling their produce, and 43 percent of all sample crop farmers anticipated difficulties in accessing inputs in the 2020 major season, mainly fertilizers and agrochemicals. Of those growing fish, 53 percent experienced difficulty in accessing inputs, mainly feeds; 60 percent reported increased input prices; and 64 percent of those harvesting from March to June 2020 experienced difficulties in selling their fish because of lower demand, lower tilapia prices, and higher transportation costs. Despite farm and nonfarm income losses, a majority of households in the rural sample reported maintaining previous levels of diet diversity and food consumption - only 11 percent reported reducing their food consumption to cope with income loss. Several months into the COVID-19 crisis in Ghana, households in both rural and urban areas showed some resilience in terms of their agricultural production and food consumption. Regular monitoring is needed, however, especially if household savings start to dry up and coping mechanisms become more restrictive.